Ancient weapons of Oman. - Clarizia, Vincenzo, (Archaeological heritage of Oman ;, 2022)
Omani men carried personal weapons until relatively recently. Swords and daggers were part of daily life attire and are still worn in social events. This book describes all the main types of Omani edged weapons, their origin, structure and accessories, with supporting illustrations and references to examples from museums and private collections.